Lëttëra web platform: A game-based learning approach with the use of technology for reading competence - Leal Uhlig, Emilia Fernanda; Garza León, Carolina; Cruz Vargas, Xóchitl; Hernández Franco, Sheila; Portuguez-Castro, May (Frontiers in Education, 2023)
Introduction This study explores the potential of technology, metacognition, and game-based learning to improve reading literacy in upper secondary school students. The focus is on the Lëttëra educational innovation, a web-based platform that uses game-based learning and technology to develop reading literacy. Methods This is a quantitative, exploratory, descriptive, and quasi-experimental study that reviewed 149 responses from high school students who took the standardized test Planea 2017. The study aimed to analyze whether using the Lëttëra platform brought a change in the students’ reading competence. The authors also examined students’ motivation toward technology, the platform interface, and the game. The data was analyzed both descriptively and inferentially. Results The results showed that using the Lëttëra platform significantly improved students’ competencies in literary text, information construction, and argumentative text. It also increased their motivation toward the proposed activities. Discussion This study demonstrates that integrating technology and game-based learning into reading instruction can lead to improved reading competencies and increased motivation among students. These findings are useful for educators, curriculum developers, and policymakers who aim to enhance reading instruction by integrating technology into their teaching practices. Conclusion Overall, this study highlights the potential of technology and game-based learning to improve reading literacy in upper secondary school students. The Lëttëra platform provides a promising approach for enhancing reading instruction, and its integration into teaching practices can benefit students, educators, and policymakers alike.